Change-supportive employee behavior: a career identity explanation. Issue 1 (9th February 2015) - Lysova, Evgenia I.; Richardson, Julia; Khapova, Svetlana N.; Jansen, Paul G. W.
Abstract : Purpose: – The purpose of this paper is to explore how career identity informs employees' willingness to engage in organizational change initiatives. Design/methodology/approach: – The paper draws on the findings of a qualitative case study exploring the experiences of 29 employees involved in a planned "bottom-up" organizational change initiative. At the time of the study, all interviewees were employed in a Dutch non-profit organization. Findings: – Drawing on protean career theory and the literature on other-oriented work values, we show that career identity informs both how employees make sense of the respective organizational change and their willingness to engage in it. The authors found that proactive career behavior and a focus on other-oriented work values inform higher levels of employees' engagement in the change, while passive career behavior and self-centered work values inform employees' lower levels of involvement in the change initiative. Based on the findings, the authors conclude this paper with a conceptual model which captures the cyclical relationship between career identity and employees' willingness to engage in organizational change initiatives. Research limitations/implications: – Future research should consider both the individual characteristics of employees involved in change initiatives and content or contextual factors when exploring willingness to engage with change. Practical implications: – Organizational change consultants and managers need to be aware of the influence of career identity on employees' willingness to engage in organizational change and use this information during the implementation of change initiatives. Originality/value: – The paper explores employees' willingness to engage with organizational change initiatives through the lens of career identity.